Controllability of Fractional Nonlinear Systems in Banach Spaces - Nirmala, R. Joice; Balachandran, K. (Journal of Applied Nonlinear Dynamics, 2026)
This paper investigates the solution of fractional dynamical systems with the inverse operator method and Mittag-Leffler function. Controllability of linear fractional dynamical systems is studied by obtaining the Grammian operator. Sufficient conditions for both nonlinear and integrodifferential systems are established by the contraction principle. Some examples are provided to illustrate the theory.